2004
DOI: 10.1097/01.crd.0000131189.50041.d1
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Therapy and Selective Estrogen Receptor Modulators for Prevention of Coronary Heart Disease in Postmenopausal Women

Abstract: Coronary heart disease is the leading cause of morbidity and mortality in women older than the age of 50 in the United States today. Traditional cardiovascular risk factors (hyperlipidemia, glucose intolerance, and hypertension) are more clearly associated with significant cardiovascular risk after menopause. The increased incidence of cardiovascular events in postmenopausal women and the evidence that cardiovascular disease on average manifests a decade later in women compared with men suggests that estrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…Therefore, in addition to the use of conventional chemotherapy and radiotherapy in the treatment of estrogen-dependent breast cancers, hormone therapy with tamoxifen may be included in the treatment regimen. Tamoxifen, a selective modulator of ER, acts as an estrogen antagonist in breast tissue [15] and an agonist in other tissues, such as in the cardiovascular system [16]. Tamoxifen is known to be cardioprotective by reducing blood levels of total cholesterol, low density lipoproteins (LDLs) [10,17], and CRP in healthy women [18] and in women with estrogen-dependent breast cancers [19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in addition to the use of conventional chemotherapy and radiotherapy in the treatment of estrogen-dependent breast cancers, hormone therapy with tamoxifen may be included in the treatment regimen. Tamoxifen, a selective modulator of ER, acts as an estrogen antagonist in breast tissue [15] and an agonist in other tissues, such as in the cardiovascular system [16]. Tamoxifen is known to be cardioprotective by reducing blood levels of total cholesterol, low density lipoproteins (LDLs) [10,17], and CRP in healthy women [18] and in women with estrogen-dependent breast cancers [19].…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, alterations in some other hormone-producing cell populations were also found in ageing female rats and women (5,(9)(10)(11). Despite some risks (12), estradiol replacement represents the classical therapeutic approach in the prevention of health problems due to ovarian hormone deficiency (13,14). Various animal models have been developed to define the space for problematising the multiple morphofunctional changes during menopause, as well as to solve the present controversies regarding the application of estradiol in humans.…”
Section: Starenje Kod žEnskog Pola Je Biološki Proces Tokom Kojeg Dolmentioning
confidence: 99%
“…We observed that the cellular and nuclear volumes of the PRL cells, and their relative volume density in this animal model of menopause Unauthenticated Download Date | 5/11/18 9:13 AM (35,45). Finally, estradiol replacement represents the classical therapeutic approach in the prevention of menopausal problems, although manifesting some risks (12)(13)(14). We used the above-mentioned menopausal rat models to critically evaluate the effects of synthetic estradiol application, and the following pituitary hormone-producing cell changes were of special interest.…”
Section: The Effects Of Estradiol Application On Pituitary Hormone-prmentioning
confidence: 99%
“…We observed that the cellular and nuclear volumes of the PRL cells, and their relative volume density in this animal model of menopause (35,45). Finally, estradiol replacement represents the classical therapeutic approach in the prevention of menopausal problems, although manifesting some risks (12)(13)(14). We used the above-mentioned menopausal rat models to critically evaluate the effects of synthetic estradiol application, and the following pituitary hormone-producing cell changes were of special interest.…”
Section: The Effects Of Estradiol Application On Pituitary Hormone-prmentioning
confidence: 99%